Quo Vadis: Payment of Compensation as an Alternative to Sanctions for Corruption Crimes Harming State Finances - Bambang Tri Bawono; Moh. Nurul Huda (Universitas Islam Sultan Agung, 2026)
Efforts to eradicate corruption through enforcement actions require high costs and overcapacity of prisons are one of the fundamental problems in handling corruption crimes in Indonesia. Based on this, new issues have emerged so that law enforcement efforts against the eradication of corruption are oriented towards the implementation of compensation to break the chain of state financial losses caused by corruption crimes. The purpose of the study is to analyze the construction of eradication of corruption crimes and the payment of compensation as an alternative to sanctions for corruption crimes. The type of research used is normative legal research, using analytical descriptive specifications and requiring primary data and secondary data. The results of the study show that compensation for corruption crimes is included in the additional type of crime, so this type of crime can only be included alternatively and cannot be when it is not accompanied by the main crime. Moreover, in the provisions of Article 4 of Law No. 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning the Eradication of Corruption Crimes, there is an article provision that expressly states that the return of state financial losses does not abolish the conviction of the perpetrators of corruption crimes and is only a mitigating factor, so the payment of compensation cannot be used as an alternative to sanctions for corruption crimes that harm state finances However, it must be accompanied by a principal crime.